Common Buckeye, Junonia coenia Hübner (Insecta: Lepidoptera: Nymphalidae) - Jaret C. Daniels (EDIS)
EENY-426, a 2-page illustrated fact sheet by Jaret C. Daniels, is part of the Featured Creatures collection. It describes this, one of the most distinctive and readily-identifiable of North American butterflies — its distribution, description, life cycle and hosts. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.